On the Growth of Solutions of Some Second-Order Linear Differential Equations. (6th March 2011) - Peng, Feng; Chen, Zong-Xuan
Abstract : We investigate the growth of solutions off ′ ′ + P ( z ) f ′ + Q ( z ) f = 0, whereP ( z ) andQ ( z ) are entire functions. WhenP ( z ) = e - z andQ ( z ) = A 1 ( z ) e a 1 z + A 2 ( z ) e a 2 z satisfy some conditions, we prove that every nonzero solution of the above equation has infinite order and hyper-order 1, which improve the previous results.